Spirituality, religious coping and perceived stress as predictors of subjective well-being in Filipino college freshmen - Laldawngsanga, Caleb (Animo Repository, 2013)
The purpose of the study was to examine spiritual well-being, religious coping (positive and negative), and perceived stress as predictors of the three components of subjective well-being (life satisfaction, positive and negative affect) among Filipino college freshmen in Metro Manila. The participants were 280 Filipino college freshmen studying in religiously affiliated private college and a public college. The sample included 117(41%) from private college while the other 163(58.2%) were from public college. Of all the participants,121(43.2%) were male students and 159(56.8% ) were female students. The participants were predominantly Catholic (80%) and their age ranged from 15-23. Four standardized instruments were used for the collection of data: Spiritual Well-Being Scale (SWBS) of Paloutzian & Ellison (1991) the Brief RCOPE of Pargament (1998) Perceived Stress Scale (PSS) of Cohen (1983) and Concise Measure of Subjective Well-being Scale (COMOSWB) of Suh & Koo (2011). Linear multiple regression was employed in this study. The findings of the study showed that spiritual well-being and perceived stress significantly predicted all the three components of subjective well-being. Positive religious coping did not significantly predict any of the three components of subjective well-being while negative religious coping significantly predicted both the affective components of subjective well-being but with some unexpected direction in the prediction results. Based on the results of the study, recommendations were made for the benefit of those in the helping profession, and also some other research possibilities in the field of subjective well-being.